Meningsfulla måltidsupplevelser : En modell för skapandet av meningsfulla måltidsupplevelser med storytelling som verktyg - Appelskog, Karin (2012)
The study describes the experience industry and experience community with a focus on food as well as current theories about experience production, which have been study at the Department of Arts, Communication and Learning at Luleå University of Technology. The essay has been prepared by a positivistic approach with an extended qualitative method theory and a deductive approach. The study is based on a literature review and qualitative interviews to find answers to how meaningful culinary experiences can be defined by an experience production perspective. The study also defines how storytelling can contribute to a meaningful culinary experience and how a restaurant can make use of storytelling to create meaningful culinary experiences for a guest. The study's object has been to develop a model that meets the purpose for this essay: "From an experience production perspective study how storytelling can be applied as a tool to create meaningful culinary experiences." Storytelling is a central concept in the model, with the aim that a restaurant can apply the model at their own business in order to create meaningful culinary experiences for a guest. The study shows that the use of storytelling can have both positive and negative aspects for a restaurant and that storytelling can be implemented in various forms and degrees in a restaurant daily operation. The study also shows that a meaningful culinary experience requires the guest to be emotionally touched and that a restaurant only can create tools for the guest to feel the meaningfulness of the culinary experience. Validerat; 20120625 (anonymous)